Assessing knowledge and self-report intention from COVID-19 symptoms based on the Health Belief Model among international students in Heilongjiang, China: a cross-sectional study. Issue 1 (11th January 2022) - Ismael, Omar Yacouba; Li, Yuanheng; Sha, Zhuowa; Wu, Qunhong; Wei, Lifeng; Jiao, Mingli; Li, Ye; Shan, Linghan; Wang, Yushu
Abstract : Background: A COVID-19 outbreak has been contained in China through effective prevention measures with the collaboration of the citizens. However, there is resistance to self-reported symptoms as required in the international student community. This study explored knowledge level and symptoms reporting behaviours toward COVID-19 among international students. Methods: An online cross-sectional investigation was conducted among 119 international students across Heilongjiang province and questionnaires implemented through WeChat between 1 and 25 March 2020. The results were explained using descriptive Χ 2 test and binary logistic regression analysis using SPSS V.20. Results: In total, 119 international students participated, with a response rate of 90.16%. Of the 119 respondents, 96 (80.7%) knew COVID-19 symptoms, 109 (91.6%) took cognisance of questions on the importance of the maintenance of wearing masks and 113 (95%) on questions regarding hand hygiene in the prevention of disease transmission. However, results show that there were still large gaps in knowledge about questions regarding the virus and the treatment methods (many participants incorrectly believed that the virus could be kill by drinking alcohol or smoking). In addition, more than half of the participants declared compliance with positive health behaviours, however 27.7% did not agree with vaccination (if any), and 31.1% did not agree to be quarantined after being diagnosed with COVID-19. Furthermore, 20 participants (16, 80%) expressed an inclination to deliberately withhold symptoms. Variables in the Health Belief Model showed a significant association with behavioural change. Conclusion: From our study, we found that there is evident knowledge about COVID-19 among international students, although orientation and sensitisation are still required. Those who were aware of the benefits of reporting, the severity of COVID-19 and the legal consequences of deliberately concealing information showed a greater willingness to report; conversely, those who believed reporting is very inconvenient and feared being quarantined after reporting showed less willingness to report. A study focusing on international students' knowledge and behaviour amid the pandemic will provide information for countries to cut off the chain of disease transmission of all variants of COVID-19.